Management strategy in increasing the effectiveness of learning in madrasas - Ulya, Najmi; Subagyo, Ahmad; Sofian, Muhammad; Susanto, Ahmad (CV. Publikasi Indonesia, 2025)
This study aims to analyze the role of strategy management in increasing the effectiveness of learning in madrasas. The effectiveness of learning is a crucial aspect in achieving educational goals, especially in the madrasa environment that has the uniqueness of values ​​and curriculum. This study explores how the implementation of strategic planning, organizing resources, implementing directed learning programs, and sustainable supervision and evaluation can contribute significantly to improving the quality and learning outcomes of students. The research method used is a literature study by analyzing various theoretical and empirical studies related to the management of strategies and the effectiveness of learning in the context of Islamic education. The results of the analysis showed that the application of adaptive and responsive strategy management principles to madrasa needs, including the involvement of all stakeholders, the development of teacher professionalism, the use of educational technology, and the creation of a conducive learning environment, has a positive correlation with increasing the effectiveness of learning. This study concluded that strategy management is not just an administrative tool, but is an important foundation in creating an effective and quality learning process in madrassas, so as to be able to produce competent and noble graduates.